Controlling the depth of anesthesia by a novel positive control strategy - Nogueira, FN (2014)
In this paper a positive control law is designed for multi-input positive systems that ensures asymptotic tracking of a desired output reference value. This control law can be viewed as a generalization of another one proposed in the literature for the control of the total mass in SISO compartmental systems, but is suitable for a wider class of positive systems. The controller proposed here is applied to the control of the depth of anesthesia (DoA), by means of the administration of propofol and remifentanil, when using a parameter parsimonious Wiener model recently introduced in the literature. Its performance is illustrated by realistic simulations.